Functionalized calcium phosphate nanoparticles to direct osteoprotegerin to bone lesion sites in a medaka (Oryzias latipes) osteoporosis model - Imangali, Nurgul; Sokolova, Viktoriya; Kostka, Kathrin; Epple, Matthias; Winkler, Christoph (Frontiers in Endocrinology, 2023)
Calcium phosphate (CaP) is the inorganic part of hard tissues, such as bone, teeth and tendons, and has a high biocompatibility and good biodegradability. Therefore, CaP nanoparticles functionalized with DNA encoding bone anabolic factors are promising carrier-systems for future therapeutic development. Here, we analysed CaP nanoparticles in a genetically modified medaka fish model, where osteoporosis-like lesions can be induced by transgenic expression of receptor activator of nuclear factor kappa-B ligand (Rankl). Rankl-transgenic medaka were used to visualize and understand effects of microinjected functionalized CaP nanoparticles during modulation of osteoclast activity in vivo. For this, we synthetized multi-shell CaP nanoparticles by rapid precipitation of calcium lactate and ammonium hydrogen phosphate followed by the addition of plasmid DNA encoding the osteoclastogenesis inhibitory factor osteoprotegerin-b (Opgb). An additional layer of poly(ethyleneimine) was added to enhance cellular uptake. Integrity of the synthesized nanoparticles was confirmed by dynamic light scattering, scanning electron microscopy and energy dispersive X-ray spectroscopy. Fluorescently labelled CaP nanoparticles were microinjected into the heart, trunk muscle or caudal fins of Rankl-transgenic medaka embryos that expressed fluorescent reporters in various bone cell types. Confocal time-lapse imaging revealed a uniform distribution of CaP nanoparticles in injected tissues and showed that nanoparticles were efficiently taken up by macrophages that subsequently differentiated into bone-resorbing osteoclasts. After Rankl induction, fish injected with Opg-functionalized nanoparticles showed delayed or absent degradation of mineralized matrix, i.e. a lower incidence of osteoporosis-like phenotypes. This is proof of principle that CaP nanoparticles can be used as carriers to efficiently deliver modulatory compounds to osteoclasts and block their activity.